Sociocultural Influences on Healthcare Inequalities Among Australian Indigenous Breast Cancer Patients - Currie, Josie; Bosco, Anthony; Currie, Geoffrey (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2025)
Healthcare inequalities among Australian Indigenous people are significantly influenced by sociocultural factors. Understanding these influences and potential solutions benefits from insights into behavioural factors in parallel with social and cultural perspectives of beliefs and attitudes. Deeper analysis of breast cancer among Indigenous women is required to better understand factors and solutions to close the inequality gap.A systematic and critical review of peer-reviewed literature was undertaken using the MEDLINE (Pubmed) electronic database. After inclusion and exclusion criteria were applied, and critical appraisal undertaken, 20 articles were identified that aligned with breast cancer incidence or survival among Indigenous Australians.The analysis revealed three central themes; pathological factors, cultural factors and social factors. Data linkage strategies reveals inequality in both incidence and 5-year survival for Indigenous breast cancer patients. Both sociocultural behaviours and sociocultural attitudes and beliefs about health, illness and healing contribute to inequality among Indigenous breast cancer patients.Poorer outcomes relate to Indigenous patients presenting with more advanced disease. Cultural and socioeconomic behaviours, attitudes and beliefs are significant barriers that create disparities between Indigenous and non-Indigenous women’s access to and engagement with breast cancer services.